Analisis Pemasaran Sagu Baruk Di Kampung Nahepese Kecamatan Manganitu Kabupaten Kepulauan Sangihe - Sasue, Gilbert; Ngangi, Charles Reijaaldo; Rori, Yolanda Pinky Ivanna (Sam Ratulangi University, 2023)
This study aims to analyze marketing channels, marketing agency functions, marketing costs, marketing margins, farmer’s share and marketing efficiency of sago baruk in Nahepese Village, Manganitu District, Sangihe Islands Regency. This research was conducted from February to April 2023, which is located in Nahepese Village. The sampling method used by farmer purposive sampling the number of respondents is 12 farmers, 3 collectors and 6 retailers. Methods of data collection carried out using primary and secondary data. The results showed that there were III (three) marketing channels. Marketing channel profit I is IDR120.000. The total margin for marketing channel II (a) is IDR30.000/bika, marketing costs are IDR8.000/bika and profit margin is IDR22.000/bika. The total margin for channel II (b) is IDR39.000/bika, marketing costs are IDR10.400/bika and profit margin is IDR28.600/bika. Channel III's total margin is IDR539.000/bika, marketing costs are IDR50.000/bika and profit margin is IDR514.000/bika. The efficiency value of marketing channel I is 0, marketing channel II (a) is 5.33%, marketing channel II (b) is 6.54% and marketing channel III is 8.41%. All of the marketing channels are efficient and marketing channel I is the most efficient.